Psychomotor activity and cognitive disruption attributable to NMDA, but not sigma, interactions in primates. - Boyce, S; Rupniak, N; Steventon, M; Cook, G; Iversen, S (1991)
We have compared the ability of phencyclidine (PCP)-like or sigma ligands to induce psychomotor effects in primates. In squirrel monkeys, administration of MK-801 (0.001-0.1 mg/kg), PCP (0.03-0.3 mg/kg), (+)-SKF10047 (0.001-3.0 mg/kg) or (-)-SKF10047 (0.1-10 mg/kg) induced ataxia, head weaving and bradykinesia. In contrast, treatment with the selective sigma ligand (+)-pentazocine using doses up to 20 mg/kg failed to induce any overt behaviours. The order of potency for induction of these behaviours was: MK-801 greater than PCP greater than (+)-SKF10047 greater than (-)-SKF10047 much greater than (+)-pentazocine. In rhesus monkeys treatment with MK-801 (0.01-0.04 mg/kg), PCP (0.05-0.2 mg/kg), (+)-SKF10047 (0.75-3.0 mg/kg) or (+)-pentazocine (1-10 mg/kg), disrupted performance of a spatial delayed response task. The potency to induce cognitive disruption was positively correlated with affinity for [3H]MK-801, but not [3H](+)-SKF10047, binding sites in vitro. These findings indicate that the psychomotor and cognitive effects of PCP-like and sigma ligands in primates are mediated through interactions at NMDA, not sigma, receptors.